Low Cost Community Health Interventions to Address the Mental Health Crisis Arising From Greece’s Financial Austerity Measures - Ramphos, Eleni; Deonandan, Raywat (Université d'Ottawa | University of Ottawa, 2014)
In response to the European financial crisis of 2008-2009, Greece reduced funding for social spending as part of its austerity program, which may have reversed past progress in Greece’s mental health system. Significant increases in depression and suicide rates coincided with the start of the crisis. A slower economic recovery may result from the combination of a less productive work force and out-migration of mental health professionals. In order to alleviate the detrimental effects of this crisis, mental health crisis training, as well as low cost community-based programs should be prioritized in Greece.